2020
DOI: 10.1002/sce.21574
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the prevailing narrative about elementary science teachers: An analysis of the experiences of science teacher enthusiasts

Abstract: The purpose of this study is to challenge the prevailing negative narrative related to elementary science teaching by investigating the experiences of elementary teachers who identify as science teacher enthusiasts (STEs). Holland, Lachiotte, Skinner, and Cain (1998)'s conception of identity as an ongoing production or construction in a socio‐cultural context served as a theoretical framing for exploring structural and personal supports and constraints related to the development of elementary teachers’ science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Akerson et al (2014), Almeida et al (2018), Archer et al (2017), Avraamidou (2016), Avraamidou (2019), Badia and Iglesias (2019), Blackmore et al (2018), Bradbury and Wilson (2020), Carrier et al (2017), Chen and Mensah (2022), Chung‐Parsons and Bailey (2019), Deneroff (2016), Eick and Reed (2002), El Nagdi et al (2018), Enyedy et al (2005), Foster and Newman (2005), Forbes and Davis (2008), Forbes and Davis (2012), Grier and Johnston (2012), Guzey and Ring‐Whalen (2018), Huang et al (2021), Jiang et al (2021a), Katz et al (2011), Keiler (2018), Madden and Wiebe (2013), Madden and Wiebe (2015), Melville and Bartley (2013), Melville et al (2013), Menon and Azam (2021), Moore (2008b), Murphy et al (2017), Olitsky (2020), Olitsky (2021), Pellikka et al (2022)*, Pedretti et al (2008), Rivera Maulucci (2008), Rivera Maulucci (2013), Rushton and Reiss (2019), Ryder and Banner (2013), Seiler (2011), Siry and Lara (2012), Tsybulsky and Muchnik‐Rozanov (2019), Varelas et al (2005), Valdés‐Sánchez and Espinet (2020), Wei and Chen (2019), Wei et al (2020), Wei et al (2021), Woolhouse and Cochrane (2010), and…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…Akerson et al (2014), Almeida et al (2018), Archer et al (2017), Avraamidou (2016), Avraamidou (2019), Badia and Iglesias (2019), Blackmore et al (2018), Bradbury and Wilson (2020), Carrier et al (2017), Chen and Mensah (2022), Chung‐Parsons and Bailey (2019), Deneroff (2016), Eick and Reed (2002), El Nagdi et al (2018), Enyedy et al (2005), Foster and Newman (2005), Forbes and Davis (2008), Forbes and Davis (2012), Grier and Johnston (2012), Guzey and Ring‐Whalen (2018), Huang et al (2021), Jiang et al (2021a), Katz et al (2011), Keiler (2018), Madden and Wiebe (2013), Madden and Wiebe (2015), Melville and Bartley (2013), Melville et al (2013), Menon and Azam (2021), Moore (2008b), Murphy et al (2017), Olitsky (2020), Olitsky (2021), Pellikka et al (2022)*, Pedretti et al (2008), Rivera Maulucci (2008), Rivera Maulucci (2013), Rushton and Reiss (2019), Ryder and Banner (2013), Seiler (2011), Siry and Lara (2012), Tsybulsky and Muchnik‐Rozanov (2019), Varelas et al (2005), Valdés‐Sánchez and Espinet (2020), Wei and Chen (2019), Wei et al (2020), Wei et al (2021), Woolhouse and Cochrane (2010), and…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…Other research studies (Akerson et al, 2014; Bradbury & Wilson, 2020) have suggested that because elementary teachers teach multiple subjects, supporting them in developing strategies for interdisciplinary instruction could enhance their multiple and possibly competing subidentities and broaden their teacher identity to include science. Because Lana developed an interdisciplinary view of science teaching vicariously, or through experiencing science as a learner in PD sessions and legitimate peripheral participation in science teaching, she began to see science more positively with interdisciplinary connections with other subjects.…”
Section: Discussionmentioning
confidence: 99%
“…System requirements can be defined briefly as pre-service teachers being informed by mentors about relevant issues. The researchers stated that according to the system requirements in science teaching, mentors should help pre-service teachers on how to conduct science teaching and how to arrange acquisitions and concepts for a good science teaching process (Bradbury & Wilson, 2020). In addition, it was emphasized that mentors should inform the pre-service teachers about the related subject in the education program of the school and the class within the framework of the system requirements .…”
Section: System Requirementsmentioning
confidence: 99%
“…On the other hand, Beck and Kosnik (2002) stated that pre-service teachers need emotional support and mentors should support them in this regard. In addition, some other studies have emphasized that science mentor teachers should know the syllabi, teaching methods and techniques, possible problems in the field and how they can be overcome and share such information with pre-service teachers (Bradbury & Wilson, 2020). However, in the study by Hudson (2007), the author stated that mentors had much more difficulty in proving mentorship on specific subjects such as science teaching, and therefore they did not feel comfortable.…”
Section: Introductionmentioning
confidence: 99%